2014
DOI: 10.1007/s12560-014-9147-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of human Noroviruses in Influent and Effluent Samples From Two Biological Sewage Treatment Plants in the Region of Monastir, Tunisia

Abstract: Noroviruses (NoVs) are responsible for numerous cases of waterborne and foodborne gastroenteritis every year. They are released in the sewage and their detection in this environment can reflect the epidemiology of the viral strains circulating in the community. A three-year (2007-2010) survey was conducted in order to evaluate the presence of human NoVs using RT-PCR in 518 sewage samples collected at the entrance and exit of two biological sewage treatment plants located in Monastir region, Tunisia. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Of note, mixed contaminations with noroviruses were detected in 125/375 (33·3%) samples (Hassine‐Zaafrane et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Of note, mixed contaminations with noroviruses were detected in 125/375 (33·3%) samples (Hassine‐Zaafrane et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Within 24 h after sample collection, the sewage samples (100 ml each) were concentrated using the adsorption‐elution method recommended by the USA Environmental Protection Agency (Lewis and Metcalf ; EPA ), as previously described (Hassine‐Zaafrane et al . ). The pellets were resuspended in 3 ml of 0·1 mol l −1 phosphate buffered saline (pH 7·2) and a solution containing 10 000 units of penicillin and 10 000 μ g of streptomycin per ml, and 25 μ g ml −1 of Fungizone was added to prevent bacterial and fungal contamination.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Studies performed in Tunisia, revealed that Group A rotavirus (RVA) was detected in 32 % of sewage samples [32]. A recent study indicated a high rate contamination of sewage samples with RV and NoV [16]. So, effective wastewater treatment processes are necessary for removal of RV [26].…”
Section: Virus Removal By Laboratory Scale Smbr Treating Abattoir Wasmentioning
confidence: 99%